The impact of small and medium-sized enterprises on the economic development of South Africa - Saah, Paul (Technium Social Sciences Journal, 2021)
The continuous rise in the number of small and medium-sized enterprises (SMEs) in South Africa in recent years, as well as their importance to economic growth, has piqued interest in this field. The aim of this research is to look into the effect of SMEs on South Africa’s economic growth. This research used a mixed-method approach, combining quantitative and qualitative methods to provide the most accurate description of the phenomena under examination. For the quantitative study, data was collected from secondary sources for the contribution of SMEs to the production of jobs as well as their contribution to South Africa’s GDP. Meanwhile, for the qualitative study, primary data was obtained from interviews. The research participants for the qualitative study were 20 proprietors and managers of small businesses. The outcome of the study discloses that SMEs make a positive impact towards economic development in terms employment creation, contribution to GDP and poverty alleviation in South Africa. The study recommends that government should formulate economic policies that will encourage the SME sector to grow by ensuring that adequate infrastructural facilities such as sufficient electricity and efficient transport systems are in place for the proper operation of SMEs.